Comparison of Databases for Complex Evidence Syntheses on Education for the Health Professions - Schaefer, Nancy; Morgan-Daniel, Jane (Medical reference services quarterly, 2023)
Increased requests for assistance with literature searches on educational topics within the health professions motivated two health science librarians to analyze search function and results in eleven bibliographic databases on questions representing three allied health instructional target populations (patient, caregiver, and future health professionals). Results overlap and relevance were estimated and useful functions and subject headings were examined, as evidence for future search and database recommendations. This research confirmed the authors' hypothesis that PubMed and CINAHL overlapped significantly yet yielded sufficient unique citations to recommend searching both, plus at least one education-specific database. For the six questions researched, psychology and sports medicine databases were less productive.